Holding on to chaos - Score, Lucy (Score, Lucy. Blue Moon series., 2025)
"Romance novelist Eva Merrill is a hot mess running from her past. She doesn't mind telling a fib or two to protect her secrets and her family. It's too bad that she moved to the nosiest small town in the world and keeps running into Sheriff Sexy-the tall, built, human lie detector. He's showing way too much interest in her and treating every conversation like it's an interrogation. Maybe that's because she accidentally showed him her boobs in the middle of downtown Blue Moon Bend. Or maybe it's because he thinks she's about to commit a crime. It's definitely not that he's attracted to her. That only happens in her novels. Donovan Cardona loves his nice, quiet hometown, and he's got some pretty strong feelings when it comes to a certain klutzy redhead, too. But his gut says she's hiding something. Just when he starts to peel back those layers to get to the naked truth, the entire town loses its collective mind-and inhibitions. Can he save the girl from her past and the town from itself?"-- Provided by publisher.